Diffuse Idiopathic Pulmonary Neuroendocrine Cell Hyperplasia (DIPNECH) in a 50-Year-Old Woman - Reza Mohseni Ahangar; Faezeh Firuzpour; Cena Aram (Case Reports in Clinical Practice)
Diffuse idiopathic pulmonary neuroendocrine cell hyperplasia (DIPNECH) is a rare pulmonary disorder characterized by hyperplasia of pulmonary neuroendocrine cells. It is frequently asymptomatic and can be challenging to differentiate from other forms of reactive pulmonary neuroendocrine cell hyperplasia (NECH). Presented is a case report of DIPNECH along with a review of the diagnosis and management. A 50-year-old female patient with a history of airway disease presented to the pulmonary ward with complaints of Functional Class III dyspnea and productive cough. The HRCT revealed the presence of multiple bilateral nodules in both lungs. The histopathology report from the nodule resection confirmed the presence of a carcinoid tumor, specifically identified as DIPNECH. As many similar cases have favorable treatment responses and satisfactory prognoses due to multidisciplinary treatment methods, the necessity of evidence-based management guidelines for DIPNECH and the accuracy of the disease definition is emphasized.